Pelaksanaan Pemenuhan Hak Anak Berhadapan dengan Hukum dalam Proses Asimilasi; Studi Literatur Review - Fatmawati Wahab; Darmawati Darmawati; Hijrah Lahalling (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This research is intended to examine and analyze the implementation of the fulfillment of children's rights in dealing with the law in the assimilation process. The type of research used in this study is a qualitative type with a normative method approach. Data collection techniques are carried out using review literature originating from statutory regulations, official records or treatises related to the discussion of a law. In addition, data collection was also carried out from several previous studies. The results of the study show that the current implementation is already under way but not yet fully in accordance with the principles of child protection. In addition, the fulfillment of the assimilation right given to correctional students should prioritize the provision of assimilation in the form of educational activities outside the fostering institution. This is so that children can adapt to the school environment when they finish serving their sentence.